Risk of Arthroplasty in Patients with Subchondral Insufficiency Fractures of the Knee: A Matched Study of the Implantable Shock Absorber using a Validated Predictive Model - Pareek, Ayoosh; Parkes, Chad W.; Slynarski, Konrad; Walawski, Jacek; Smigielski, Robert; Merwe, Willem van der; Krych, Aaron J. (The Journal of Knee Surgery, 2023)
Subchondral insufficiency fractures of the knee (SIFK) can result in high rates of osteoarthritis and arthroplasty. The implantable shock absorber (ISA) implant is a titanium and polycarbonate urethane device which reduces the load on the medial compartment of the knee by acting as an extra-articular load absorber while preserving the joint itself. The purpose of this study was to evaluate whether partially unloading the knee with the ISA altered the likelihood of progression to arthroplasty utilizing a validated predictive risk model (SIFK score). A retrospective case-control (2:1) study was performed on patients with SIFK without any previous surgery and on those implanted with the ISA with the primary outcome being progression to arthroplasty compared with nonoperative treatment at 2 years. Baseline and final radiographs, as well as magnetic resonance imagings, were reviewed for the evaluation of meniscus or ligament injuries, insufficiency fractures, and subchondral edema. Patients from a prospective study were matched using the exact SIFK Score, a validated predictive score for progression to arthroplasty in patients with SIFK, to those who received the ISA implant. Kaplan–Meier analysis was conducted to assess survival. A total of 57 patients (38 controls:19 ISA) with a mean age of 60.6 years and 54% female were included. The SIFK score was matched exactly between cases and controls for all patients. The 2-year survival rate of 100% for the ISA group was significantly higher than the corresponding rate of 61% for the control group (p < 0.01). In ISA, 0% of the patients converted to arthroplasty at 2 years, and 5% (one patient) had hardware removal at 1 year. When stratified by risk, the ISA group did not have a significantly higher survival compared with low-risk (p = 0.3) or medium-risk (p = 0.2) controls, though it had a significantly higher survival for high-risk groups at 2 years (100 vs. 15%, p < 0.01). SIFK of the medial knee can lead to significant functional limitation and high rates of conversion to arthroplasty. Implants such as the ISA have the potential to alter the progression to arthroplasty in these patients, especially those at high risk.
Keywords: root tears; subchondral insufficiency fracture; SONK; SIFK; spontaneous osteonecrosis